Politik Identitas Bangka Belitung Dan Multikulturalisme Pada Film Laskar Pelangi - Mohamad Aidil; Kustiawan; fajri, Muhammad Fajri; Benni Saputra; Zahru Latip; Ahlam Najib; Zara Alga Suri; Hairul; Heru Ilham Patria (Jurnalika : Jurnal Ilmu Komunikasi, 2024)
This research analyzes the representation of identity politics and multiculturalism in the film Laskar Pelangi which is adapted from the novel by Andrea Hirata. Using film analysis and literature research, this research identifies themes of identity politics and multiculturalism expressed in the film's narrative, dialogue and imagery. The research results show that identity politics in the film Laskar Pelangi is reflected through ethnic and religious diversity, unity in diversity, local Malay identity, the role of education as a unifying tool, economic and social disparities, as well as the influence of colonial and local history. Multiculturalism is described through ethnic diversity, friendship across identities, the use of diverse languages and dialects, diversity of celebrations and traditions, equality in education, tolerance of teachers, economic and social interactions, and diversity of family dynamics. This film provides a positive picture of how different identities can unite and become a driving force in achieving common goals through education and solidarity. Overall, Laskar Pelangi shows the importance of building an inclusive and dynamic society by respecting cultural diversity.